Mitochondria and sensory processing in inflammatory and neuropathic pain - Silva Santos Ribeiro, P.; Willemen, Hanneke L. D. M.; Eijkelkamp, Niels (Frontiers in Pain Research, 2022)
Rheumatic diseases, such as osteoarthritis and rheumatoid arthritis, affect over 750 million people worldwide and contribute to approximately 40% of chronic pain cases. Inflammation and tissue damage contribute to pain in rheumatic diseases, but pain often persists even when inflammation/damage is resolved. Mechanisms that cause this persistent pain are still unclear. Mitochondria are essential for a myriad of cellular processes and regulate neuronal functions. Mitochondrial dysfunction has been implicated in multiple neurological disorders, but its role in sensory processing and pain in rheumatic diseases is relatively unexplored. This review provides a comprehensive understanding of how mitochondrial dysfunction connects inflammation and damage-associated pathways to neuronal sensitization and persistent pain. To provide an overall framework on how mitochondria control pain, we explored recent evidence in inflammatory and neuropathic pain conditions. Mitochondria have intrinsic quality control mechanisms to prevent functional deficits and cellular damage. We will discuss the link between neuronal activity, mitochondrial dysfunction and chronic pain. Lastly, pharmacological strategies aimed at reestablishing mitochondrial functions or boosting mitochondrial dynamics as therapeutic interventions for chronic pain are discussed. The evidence presented in this review shows that mitochondria dysfunction may play a role in rheumatic pain. The dysfunction is not restricted to neuronal cells in the peripheral and central nervous system, but also includes blood cells and cells at the joint level that may affect pain pathways indirectly. Pre-clinical and clinical data suggest that modulation of mitochondrial functions can be used to attenuate or eliminate pain, which could be beneficial for multiple rheumatic diseases.